Effect of Biocontrol Agent (Bacillus and Mycorrhizal Fungi) Application against Twisted Disease (Fusarium spp.) in Off-Season Shallot Production - Wibowo, Eko Prasetyo; Widiastuti, Ani; Joko, Tri; Suryanti, Suryanti; Priyatmojo, Achmadi (Universitas Gadjah Mada, 2022)
The demand for shallots has increased along with the Indonesian population. To achieve shallot production goals, farmers began to plant shallots outside usual planting season. However, unfavourable environmental conditions and pest attacks are obstacles faced by farmers. The use of Biological Control Agents (BCA) is a way to improve plant growth and protect plants against plant pathogens or even abiotic stresses. The purpose of this study was to evaluate the response of shallot plants after BCA (Bacillus and Mycorrhizal Fungi) application, especially against twisted disease during off-planting season. This research was conducted by preparing BCA isolates, applying BCA, measuring disease incidence and intensity, observing plant growth development, analyzing phenol content, and analyzing phosphate content. Results showed BCA Bacillus and mycorrhizal fungi did not inhibit Fusarium spp. infection. Agronomic measurements showed no significant difference in crown weight and root weight, but isolate B8 significantly increase the number of leaves while isolate M significantly decreased plant height. Isolates B6, B7, and M significantly reduced the total phenol content in shallot plants. Phosphate analysis on isolate M did not have significant effects on shallot plants, while BCA Bacillus and Mycorrhizal fungi application could not suppress twisted disease. Nevertheless, B8 treatment has the potential to increase shallot growth; therefore, further research must be conducted.